(untitled) (Journal of Foreign Language Studies, 2025)
This study aims to provide a holistic picture of first-year students’ attitudes towards the use of Vietnamese (L1) in English (L2) classrooms and examines whether background factors such as geographical locations and types of high school influence their attitudes. A quantitative research approach was employed, involving a questionnaire survey of 107 first-year students at a university in Vietnam. The findings reveal that the students hold relatively positive attitude towards the use of L1, while acknowledging both its advantages and limitations in L2 classrooms. However, no significant differences in attitudes were found among students from different regions or high school types, suggesting that these factors do not significantly impact university students’ attitudes towards the use of L1 in English learning contexts.